Talent identification in professional soccer players according to their birth date - Rahnama, N.; Bambaeichi, E.; Sadeghipour, H. R. (World Journal of Sport Sciences, 2009)
Some studies showed that most professional soccer players were born on the same date. The aim of this study was to investigate talent identification among players of the 2006 FIFA World Cup according to the distribution of their birth date in different playing positions in five continents of the world. Information about birth dates of 736 players was collected from FIFA website. Chi Squire test and ANOVA were used to assess the differences among the players' birth dates. The results showed no significant effect in different positions between players born in the first and second halves of month and between players born in different months (P>0.05). Although the births between August and October were more than other seasons, the difference was not significant (P>0.05). Also, no significant effect was found between different positions and the players' birth season (P>0.05). No significant effect was found between month and season of births in five continents (P>0.05). Although the mean of height and the mean of weight of the players born between August and October were more than other seasons, this difference was not significant (P>0.05). It can be concluded that birth date of players of the 2006 FIFA World Cup was similar to the distribution of playing positions and continents. Talent identification according to the birth date is not reliable.